THE VALUE OF MISOPROSTOL IN PATIENTS USING NSAIDs - Levent DEMİRTÜRK,; Saadeddin HÜLAGÜ,; İlhan KARABEKİR,; Sabahattin GÜL,; Zeki ÇANKIR,; Mehmet ALTIN,; Metin ERTÜRK, (Turkish Journal of Gastroenterology, 2020)
-